Analisis Film Animasi Spongebob Squarepants Ditinjau Dari Nilai-Nilai Akhlak Dalam Islam - Muhamad Al Fachry; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2022)
Spongebob Squarepants is so popular and has had many airtimes on Indonesian TV stations over the years, this will certainly have an impact on connoisseurs, especially in terms of morals. This study aims to analyze what Islamic moral values are in this film. There are two scopes of morals that will be described, namely morals to others and the environment. The method used is qualitative with the type of content analysis. Based on the results of research observations in the animated film Spongebob Squarepants contains Islamic moral values, each character in the film has dominant morals from the good side, such as loving others such as loving yourself, treating animals well, and bad sides, such as liking to disturb neighbors and exploiting animals.